Production systems in the Blue Nile Basin: implications for environmental degradation and upstream and downstream linkages - Haileslassie, Amare; Hagos, Fitsum; Awulachew, Seleshi Bekele; Peden, Donald G.; Gebreselassie, S.; Negash, F. (2008)
The Blue Nile Basin (Abay in Ethiopia) covers wide range landscapes and climatic zones in Ethiopia and Sudan. Different agricultural production systems, in the basin, evolved in response to those diverse landscapes and climatic zones, and the attendant human decision dynamics that responds to changing livelihood opportunities. Many production systems studies recognized only mixed agriculture in the highlands and pastoralism in the lowland areas. Now it is widely recognized that several other factors such as land-use, vegetation cover, and different land and water management practices are important in defining production systems. These study approaches help to capture the diverse water and land related livelihoods of the farming communities in upstream and downstream parts of the basin and their impact on their respective environments. In this review, we follow a similar approach but focus at the basin scale to define and characterize major production systems and associated subsystems specifically: small grain cereals-based mixed crop-livestock and maize-sorghum-perennials systems and their associated subsystems. We then focus on water management practices in rainfed and irrigated systems. We also synthesized impacts of those production systems on the environment and upstream-downstream linkage using erosion, sedimentation, livestock and crop water productivity, soil nutrient balances as indicators. Evidences suggest that natural ecosystem services (e.g. regulation services such as nutrient recycling and redistribution) are severely threatened in the Blue Nile basin. On-site and off-site effects of pedogenic processes like sediment removal, transportation, redistribution and attendant environmental impacts (e.g. nutrient balances and water productivity) are highly correlated with dominant farming practices and attendant anthropogenic interventions. Indicators such as water productivity and soil nutrient depletion and farmers? activities to replenish the lost nutrients are also strongly related to the degree of the farmers? resource endowments. In view of initiating the upstream community to invest more on land and water management, options for payment for environmental services (PES) must be sought and, interventions that enhance sustainable ecosystem management must use integrated approaches and farming system/subsystems as entry point.